(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Saifudin, Shafira S, Dwiranti A, Salamah A. 2021. Short Communication: Analysis of the chromosome numbers of Zinnia elegans Jacq. in single, double, and pom-pom flowers. Biodiversitas 22: 2771-2777. Zinnia elegans Jacq. is highly valued as an ornamental plant with a variety of flower colors, sizes, and shapes. Polyploidization has been reported in Z. elegans with pom-pom flowers, nevertheless, the variation in chromosome numbers of various flower shapes has yet to be investigated. This study aimed to analyze the chromosome numbers of Z. elegans Jacq. cultivar “California Giant,” “Lilliput,” and “Cactus Flowered Mix” with single, double, and pom-pom flowers to determine their variations and identify the morphology of the flowers. Chromosomes were prepared using the squashing method, and images were analyzed using the Chromosome Image Analyzing System (CHIAS) IV. The minimum of 5 slides was prepared for each flower type from each cultivar. The results show that the three cultivars are diploid plants (2n = 24) with varying flower morphology. The single and double flowers of Z. elegans “Lilliput” and the single flower of “Cactus Flowered Mix” showed no variation in chromosome numbers. In contrast, chromosome number variation was found in the pom-pom flower of Z. elegans “California Giant” (2n = 22, 24, 48) and the double flower of “Cactus Flowered Mix” (2n = 9, 13, 15, 24). Two cultivars, Z. elegans “California Giant” and Z. elegans “Cactus Flowered Mix,” were successfully analyzed using CHIAS IV. Statistical analysis using a t-test (? = 0.05) showed that the total chromosome length of Z. elegans “California Giant” (2n = 24) was significantly greater than that of Z. elegans “Cactus Flowered Mix” (2n = 24). Chromosome satellites were found in both cultivars.